Filsafat Islam, Tasawuf dan Ilmu Kalam: Tinjauan Historis - Khasanah, Siti Uswatun (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2024)
Sufism, philosophy and kalam science are often differentiated and separated from knowledge, as if the three of them have no ties or ties to history. Even though at the beginning of their appearance, the three of them were united and had a relationship. This research explains the relationship between Islamic Philosophy, Sufism and Kalam Science (historical overview). This research is library research. The formulation of the problem to be answered in this research is: 1) What is the relationship between Islamic philosophy, Sufism and kalam science? 2) what is the scope of Islamic philosophy, Sufism and kalam science. The research method used in this research is descriptive-analysis. The research results show that: 1) the relationship between Islamic philosophy, Sufism and kalam science is interrelated and has a relationship in the discussion of truth, namely: in Sufism, the essence of truth is revelation (kasyaf), revelation, true truth (Allah) through the eyes of the heart. Sufism finds the truth by going through many paths or methods. Meanwhile, the truth of Kalam science is in the form of understanding the truth of religious teachings through logical reasoning that refers to the text of the Qur'an and Hadith, while the truth in philosophy is philosophy lies in the search for the essence. 2) The scope of kalam regarding faith, disbelief and its manifestations, hypocrisy and its limitations. In Sufism, about practical ways or methods to experience faith and peace. Sufism is the search for a spiritual path, unity with absolute truth and mystical knowledge according to the path and sunnah. While philosophy does not only refer to rationalist philosophy in motion, but also to all intellectual currents of Islamic culture which seek to achieve knowledge of the original causes through the power of wisdom